Total Intravenous Anesthesia for Coronary Artery Bypass Grafting: A Case Report of Successful Hemodynamic Management and Early Recovery - Sriwahyuniati Purwaningsih; Anas Alatas; Yudi Hadinata (Eduvest - Journal of Universal Studies, 2026)
Coronary artery bypass grafting (CABG) is a complex cardiac surgical procedure that requires precise anesthetic management to maintain hemodynamic stability and support optimal postoperative recovery. Total intravenous anesthesia (TIVA) has emerged as an alternative anesthetic technique in cardiac surgery due to its advantages in anesthetic titration, hemodynamic control, and facilitation of fast-track recovery protocols. This case report aimed to describe the application of TIVA in a high-risk CABG patient and evaluate its effectiveness in achieving intraoperative stability and early postoperative recovery. A case report was conducted involving a 66-year-old male patient with three-vessel coronary artery disease who underwent CABG at the National Cardiovascular Center Harapan Kita, Jakarta. Clinical data were collected from preoperative assessments, intraoperative anesthesia records, hemodynamic monitoring parameters, and postoperative intensive care management in accordance with the CARE guidelines. The patient received TIVA using propofol, sufentanil, and rocuronium, supported by multimodal monitoring, including the Bispectral Index (BIS), Near-Infrared Spectroscopy (NIRS), arterial line monitoring, and central venous catheter monitoring. The results demonstrated stable intraoperative hemodynamic conditions with appropriate vasoactive support using dobutamine and nitroglycerin. The patient successfully underwent early extubation eight hours after surgery, with acceptable postoperative laboratory parameters and no significant anesthetic complications. In conclusion, TIVA combined with comprehensive hemodynamic monitoring and fast-track protocols provided effective anesthetic management for CABG, supporting cardiovascular stability and early recovery. Further studies involving larger patient populations are required to confirm its broader clinical benefits.